1992
DOI: 10.1021/bi00141a019
|View full text |Cite
|
Sign up to set email alerts
|

EcoRV restriction endonuclease: communication between DNA recognition and catalysis

Abstract: A genetic system was constructed for the mutagenesis of the EcoRV restriction endonuclease and for the overproduction of mutant proteins. The system was used to make two mutants of EcoRV, with Ala in place of either Asn185 or Asn188. In the crystal structure of the EcoRV-DNA complex, both Asn185 and Asn188 contact the DNA within the EcoRV recognition sequence. But neither mutation affected the ability of the protein to bind to DNA. In the absence of metal ion cofactors, the mutants bound DNA with almost the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 39 publications
4
45
0
Order By: Relevance
“…However, the exonuclease activity of the D157N mutant is increased when magnesium chloride is replaced by manganese chloride. A similar increase in activity when Mn 2ϩ replaced Mg 2ϩ has been reported for the active site mutants of EcoRV (18) and BamHI (19) restriction endonucleases. For both the D200N and D157N mutant proteins, the ratio of trinucleotide to dinucleotide products released is lower than that of the wild type protein in Mg 2ϩ ( Fig.…”
Section: Discussionsupporting
confidence: 77%
“…However, the exonuclease activity of the D157N mutant is increased when magnesium chloride is replaced by manganese chloride. A similar increase in activity when Mn 2ϩ replaced Mg 2ϩ has been reported for the active site mutants of EcoRV (18) and BamHI (19) restriction endonucleases. For both the D200N and D157N mutant proteins, the ratio of trinucleotide to dinucleotide products released is lower than that of the wild type protein in Mg 2ϩ ( Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Rather, all the protein-DNA contacts are intimately connected to each other and additionally to the metal ion binding site and to important catalytic residues. Previously it has been shown that DNA recognition is closely coupled to both metal ion binding (42) and catalysis (43), and this study demonstrates that phosphate groups are also critically involved in these processes.…”
Section: Role Of Phosphates In the Ecorv Endonuclease-catalyzedsupporting
confidence: 58%
“…This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C. protein and the GATATC bases, have been probed using alternative sequences (40,42,49), base analogues (13-15, 50 -53), and site-directed mutagenesis (43,54), and many have been shown to be essential for efficient catalysis. The endonuclease also makes extensive contacts to the phosphate backbone (38,39).…”
mentioning
confidence: 99%
“…A recent report indicates that EcoRV can bind to DNA in the absence of Ca 2ϩ or Mg 2ϩ under different conditions (44); attempts to visualize a gel shift for PvuII in the absence of metal ions or in the presence of Mg 2ϩ for the catalytically inactive mutants have thus far been unsuccessful. Similar mutagenesis studies have been done on EcoRI (10 -13, 15, 45), EcoRV (18,20,23,24,28), and BamHI (26,27,30). These studies have anticipated or confirmed the predicted roles of residues identified as central from the crystal structures of the respective enzymes.…”
Section: Discussionmentioning
confidence: 63%